Brainstem auditory evoked potentials in children with microcephaly - Irawan Mangunatmadja; Dwi Putro Widodo; Hardiono D Pusponegoro (Paediatrica Indonesiana, 2003)
Background Hearing loss (HL) is commonly found in childrenwith microcephaly. The aim of this study was to reveal hearing lossand auditory brainstem pathways disorders in children with micro-cephaly and other handicaps.Methods There were 194 children who were referred for hearingevaluation. Subjects with history of congenital perinatal infection(TORCH) were excluded. Data were collected from the results ofBrainstem Auditory Evoked Potentials (BAEP) recordings, includ-ing sex, age, clinical manifestations, latency and interlatency be-tween waves I, III, V, and the hearing levels of each ear.Results Moderate to profound HL were found in fourteen ears(58%) of patients with microcephaly. Moderate to profound HL (28%)and endocochlear damage (15%) were found in the ears of pa-tients with microcephaly and delayed speech. Moderate to pro-found HL (39%) and endocochlear damage (11%) were detectedin the ears of patients with microcephaly and delayed develop-ment. Moderate to profound HL (21%) and endocochlear damage(16%) were found in the ears of microcephalic patients with bothdelayed speech and delayed development. Moderate to profoundHL (26%) and endocochlear damage (32%) were detected in theears of patients with microcephaly and cerebral palsy.Conclusion This study revealed the importance of early HL de-tection in microcephalic patients especially those with other handi-caps such as delayed speech, delayed development, and cere-bral palsy